Development and content validation of STIL.sg instrument for measuring system thinking and generic science skills in socio-technical contexts - Meiry Akmara Dhina; Ida Kaniawati; Ade Gafar Abdullah; Lilik Hasanah; Sugeng Rifqi Mubaroq (Education and Development Research, 2026)
This research presents the systematic development of the STIL.sg instrument for measuring System Thinking and Generic Science Skills in Socio-Technical Inquiry Learning contexts, followed by rigorous content validation through structured expert judgment. Using Evidence-Centered Design approach, a 27-item multiple-choice instrument was first developed based on established theoretical frameworks; the instrument was subsequently subjected to content validation by a panel of domain experts. Content validation involved five experts from science education, learning evaluation, and pharmacy fields. The Content Validity Ratio (CVR) values ranged from 0.68 to 0.94, with an overall Content Validity Index (CVI) of 0.784, indicating excellent content validity. Modified Kappa coefficients (κ) ranged from 0.65 to 0.89, confirming inter-rater reliability. Physical pharmacy was chosen as the application context due to its interdisciplinary nature requiring both systematic thinking and fundamental scientific skills. The developed instrument demonstrates strong theoretical foundation and expert consensus, providing a tool with strong evidence of content validity for measuring complex cognitive skills in applied science education.